Vpliv koncentracije površinsko aktivnega sredstva in reološkega dodatka na reološke lastnosti vodnih suspenzij TiO2 - Florjančič, Urška (Kovine zlitine tehnologije, 1998)
The influence of different concentrations of the surfactant and the rheological additive on the rheological properties of the aqueous paints intended for the dip coating process in an industrial product line was investigated under different steady shear conditions. The controlled rate rotational rheometer was employed. Different experimental procedures were carried out in order to examine the flow properties under conditions similar to real situations in technological processes. The investigated paints exhibited non-Newtonian flow behaviour of the shear thinning and the viscoelastic properties. The characterization of such complex industrial suspensions represents a fundamental bais for establishing appropriate experimental procedures to be used in industrial labs for the formulation, as well as for the product control and optimisation of products.
Keywords: reologija; titanov dioksid; površinsko aktivne snovi; suspenzije